The "Glass of Milk" Subsidy Program and Malnutrition in Peru - Stifel, David (World Bank, Washington, DC, 2014)
The authors evaluate the Vaso de Leche (VL) feeding program in Peru. They pose the question that if a community-based multistage targeting scheme such as that of the VL program is progressive, is it possible that the program can achieve its nutritional objectives? The authors address this by linking VL public expenditure data with household survey data to assess the targeting, and then to model the determinants of nutritional outcomes of children to see if VL program interventions have an impact on nutrition. They confirm that the VL program is well targeted to poor households and to those with low nutritional status. While the bulk of the coverage of the poor is attributed to targeting of poor districts, the fact that the poor receive larger in-kind transfers is attributed to intradistrict targeting. But the impact of these food subsidies beyond their value as income transfers is limited by the degree to which the commodity transfers are inframarginal. The authors find that transfers of milk and milk substitutes from the VL program are inframarginal for approximately half of the households that receive them. So, it is not entirely surprising that they fail to find econometric evidence of the nutritional objectives of the VL program being achieved. In models of child standardized heights, the authors find no impact of the VL program expenditures on the nutritional outcomes of young children-the group to whom the program is targeted.